Infant death due to CMV enterocolitis. (15th June 2012) - Refai, Zafer; Nicholls, Stuart; Garg, Anil
Abstract : An infant was admitted with symptoms of diarrhoea and vomiting. After initial improvement she unexpectedly died. Postmortem confirmed a diagnosis of cytomegalovirus (CMV) enterocolitis. The authors report this case and review other published cases of immunocompetent infants who presented with this infection. Clinicians should consider stool CMV PCR test or referral for endoscopy and biopsy in young babies who present with profuse and prolonged episodes of diarrhoea. The value of ganciclovir in immunocompetent infants who suffer with CMV gastrointestinal involvement is still not clear.